Thinking sociologically - Bauman, Zygmunt 1925-2017; May, Tim 1957- (Wiley Blackwell, 2019)
Now in its third edition, Thinking sociologically continues to offer a stimulating exploration of the underlying assumptions and tacit expectations which structure our view of the world. The authors explore key concepts in sociology, review recent developments in society and examine the applicability of sociology to everyday life. The world has changed a great deal since the second edition's publication. Issues of climate change, sustainability, inequality, social justice, inclusion and the role of social media have risen to prominence, and we are collectively challenging our ways of thinking about intimacy, community, consumption, ethics, social identity, and more. This new third edition has been revised to reflect these and other transformations in our lives, helping us to think sociologically about the consequences of these burgeoning issues, how we organize our societies, understand ourselves and lead our lives. Written for undergraduates, postgraduates, practicing sociologists and social scientists, this book also holds a broad appeal to a general audience. The third edition of Thinking sociologically offers a compelling survey of sociological issues, recent changes in society and their influence on our day-to-day lives and identities.